Left and right ventricular strain using fast strain-encoded cardiovascular magnetic resonance for the diagnostic classification of patients with chronic non-ischemic heart failure due to dilated, hypertrophic cardiomyopathy or cardiac amyloidosis - Steen, Henning; Giusca, Sorin; Montenbruck, Moritz; Patel, Amit R.; Pieske, Burkert; Florian, Andre; Erley, Jennifer; Kelle, Sebastian; Korosoglou, Grigorios (Journal of cardiovascular magnetic resonance, 2021)
To compare the ability of left ventricular (LV) and right ventricular (RV) strain measured by fast-strain encoded cardiovascular magnetic resonance (CMR) (fast-SENC) with LV- and RV-ejection fraction for the diagnostic classification of patients with different stages of chronic heart failure (stages A-D based on American College of Cardiology/American Heart Association guidelines) due to non-ischemic cardiomyopathies.